Phase II trials in heart failure: The role of cardiovascular imaging - Shah, Sanjiv J. (2011)
The development of new therapies for heart failure (HF), especially acute HF, has proven to be quite challenging; and therapies evaluated in HF have greatly outnumbered treatments that are eventually successful in obtaining regulatory approval. Thus, the development of therapies for HF remains a vexing problem for pharmaceutical and device companies, clinical trialists, and health care professionals. Nowhere is this more apparent than in the phase II HF clinical trial, in which the goal is to determine whether an investigational agent should move forward to a phase III trial. Recent advancements in noninvasive cardiovascular imaging have allowed a new era of comprehensive phenotyping of cardiac structure and function in phase II HF trials. Besides using imaging parameters to predict success of subsequent phase III outcome studies, it is essential to also use imaging in phase II HF trials in a way that increases understanding of drug or device mechanism. Determination of the patients who would benefit most from a particular drug or device could decrease heterogeneity of phase III trial participants and lead to more successful HF clinical trials. In this review, we outline advantages and disadvantages of imaging various aspects of cardiac structure and function that are potential targets for therapy in HF, compare and contrast imaging modalities, provide practical advice for the use of cardiovascular imaging in drug development, and conclude with some novel uses of cardiac imaging in phase II HF trials.